Numerical modeling and experimental validation of fluid flow in micro- and meso-fluidic siphons - Akhras, Nour; Singh, Gurjas; Gill, Kirandeep K.; Bola, Shaan; Al-Hakeem, Kareem; Reis, Nuno M. (Frontiers in Chemical Engineering, 2024)
Siphons have been used for thousands of years to transfer fluids without the use of pumps or power and are present in our daily lives. Paradoxically, it is only in recent decades that the operation of siphons has been fully clarified, which is now understood to be exclusively linked to gravity and molecular cohesion. Siphons are uniquely able to offer automatic, intermittent flow, yet present the main drawback of requiring a source of energy to induce initial flow. Our research team has recently disclosed a microfluidic siphon able to self-prime and deliver a sequence of bioanalytical reagents, previously demonstrated for high-performance, multi-reagents diagnostic testing. Here we show for the first time 2D and 3D computational fluid dynamics (CFD) modeling and the experimental characterization of fluid flow in a range of miniaturized hydrophilic siphons of varying hydraulic liquid height-to-length ratios, ΔH/LT = 0–0.9, using fluids of varying viscosities. CFD simulations using velocity- and pressure-driven inlet boundary conditions were generally in good agreement with experimental fluid flow rates and pressure-balance predictions for plastic ∼0.2 mm and glass ∼0.6 mm internal diameter microfluidic siphons. CFD predictions of fluid flow in “meso-scale” siphons with 1 and 2 mm internal diameters also fully matched normalized experimental data, suggesting that miniaturized siphons are scalable. Their discharge rate and pressure drop are readily predicted and fine-tunable through the physical properties of the fluid and some design parameters of the siphon. The wide range of experimental and numerical parameters studied here provide an important framework for the design and application of gravity-driven micro- and meso-fluidic siphons in many applications, including but not limited to life sciences, clinical diagnostics, and process intensification.